Preserving Malay heritage: basic understanding of the traditional boats making in Terengganu - Kamaruddin, Norfadilah; Rosli, Hafizah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Traditional ways of making boats are slowly fading because many things have changed since the modern age began. As technology improves worldwide, this study attempts to discover how traditional boats are made in Terengganu. It also suggests a way to keep future generations aware of how traditional boats are made. This study employed a depth interview with a shipwright and field observations at the Terengganu State Museum as part of a qualitative research method. They discussed the fundamental procedure used to make all different types of traditional boats from Terengganu. The findings of this study established a possible medium for preserving Malay Heritage.